2012
DOI: 10.1103/physrevb.86.144529
|View full text |Cite
|
Sign up to set email alerts
|

Dephasing of Cooper pairs and subgap electron transport in superconducting hybrids

Abstract: We argue that electron-electron interactions fundamentally restrict the penetration length of Cooper pairs into a diffusive normal metal (N) from a superconductor (S). At low temperatures, this Cooper pair dephasing length L ϕ remains finite and does not diverge at T → 0. We evaluate the subgap conductance of NS hybrids in the presence of electron-electron interactions and demonstrate that this length L ϕ can be directly extracted from conductance measurements in such structures. It is well known that a normal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…Indeed, through different strain, orientation, and thickness configurations one can achieve two and three dimensional topological insulator and DSM states in α-Sn thin films [14][15][16]. The ability to produce and process high quality Sn films will be a significant boon in achieving the diverse applications of topological physics such as efficient nonvolatile memory and low voltage devices [17][18][19][20]. The persistence of the topological states near room temperature could enable these applications to be employed in all manner of environments [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, through different strain, orientation, and thickness configurations one can achieve two and three dimensional topological insulator and DSM states in α-Sn thin films [14][15][16]. The ability to produce and process high quality Sn films will be a significant boon in achieving the diverse applications of topological physics such as efficient nonvolatile memory and low voltage devices [17][18][19][20]. The persistence of the topological states near room temperature could enable these applications to be employed in all manner of environments [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant energy scale in the case of 3DTIs lie in the terahertz (THz) region and there have been already interesting reports on the THz radiation from the bulk [8]. Some of the developments in the direction of THz related studies are helicity-controlled photocurrents [9][10][11], THz quantum Hall effect of Dirac fermions [12], giant photocurrent at cyclotron resonance in a THz radiation [13,14], magneto-oscillations of THz radiation-induced photocurrent [15], anisotropy photogalvanic effects by the THz electric field [16], and tunable photogalvanic effect via proximity interaction with illumination of THz radiation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Many theoretical works have studied heterostructures consisting of TIs and ferromagnetic (FM) insulators, focusing in particular on the effects on the magnetization in the magnetic layer. [9][10][11][12][13][14][15][16][17][18][19][20] One recent study focused instead on the effective interactions between Dirac fermions on the surface of a TI coupled to a FM insulator with mean field magnetization perpendicular to the TI surface. 21 It showed that interactions between the Dirac fermions and the transverse magnons in the FM lead to an effective attractive pairing between fermions with parallel momenta, so-called Amperean pairing.…”
Section: Introductionmentioning
confidence: 99%